Sosialisasi Literasi Keuangan Bagi Anggota Paguyuban Pemandian Alam Sejuk (PAS) di Kabupaten Simalungun - Pawer Darasa Panjaitan; Darwin Damanik; Bagudek Tumanggor (Jurnal Pengabdian Masyarakat Sapangambei Manoktok Hitei, 2022)
The development of tourism in Simalungun Regency after the Covid 19 pandemic has started to get excited again, one of the attractions is the Pemandian Alam Sejuk (PAS) in Nagori Mariah Jambi. Paguyuban PAS is the manager of this tourist attraction. The development of this tourism object is still a lot of obstacles, one of which is fundamentally the problem of understanding financial literacy from Paguyuban PAS Members. This community service activity aims to provide understanding and education about the importance of financial literacy and good tourism management for Paguyuban PAS members. Based on the results of activities in the socialization of financial literacy and tourism management for Paguyuban PAS members, it can be concluded that the PAS Paguyuban members have low understanding of financial literacy, PAS Paguyuban members have low understanding in managing tourism objects properly, and the local government is not paying attention to providing infrastructure. and facilities around the PAS tourist area